Determining the rotational velocity of gas-metal multicomponent plasma in a reflex discharge - Kovtun, Yu.V.; Skibenko, A.I.; Skibenko, E.I.; Larin, Yu.V.; Yuferov, V.B. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
For the first time the rotational velocity of plasma layers with np = ncr^1,2 in the gas-metal plasma medium of the reflex discharge was determined using the two-frequency microwave fluctuation reflectometry. The measurement results demonstrated that the angular frequency of plasma layer rotation is varying and therefore the plasma rotates not as a single whole. The maximum rotation velocity increases with magnetic field increasing. The values of the electric field strength in two layers and the plasma particle separation coefficient α were determined.